2021
DOI: 10.3390/microorganisms9061228
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Susceptibility to Miltefosine of Leishmania infantum (syn. L. chagasi) Isolates from Different Geographical Areas in Brazil

Abstract: Treatment of visceral leishmaniasis in Brazil still relies on meglumine antimoniate, with less than ideal efficacy and safety, making new therapeutic tools an urgent need. The oral drug miltefosine was assayed in a phase II clinical trial in Brazil with cure rates lower than previously demonstrated in India. The present study investigated the susceptibility to miltefosine in 73 Brazilian strains of Leishmania infantum from different geographic regions, using intracellular amastigote and promastigote assays. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
(56 reference statements)
3
5
0
1
Order By: Relevance
“… 32 Subsequently, it was found that deletion of the MSL (miltefosine susceptible locus) on chromosome 31 of the parasite was significantly correlated with miltefosine treatment failure. 33 Nevertheless, a recent study was unable to demonstrate a correlation between the absence of MSL, in L. infantum isolates from a collection, and the in vitro resistance phenotype, 34 identified in our Phase 2 clinical trial well characterized isolates. 32 , 33 …”
Section: Introductionmentioning
confidence: 70%
“… 32 Subsequently, it was found that deletion of the MSL (miltefosine susceptible locus) on chromosome 31 of the parasite was significantly correlated with miltefosine treatment failure. 33 Nevertheless, a recent study was unable to demonstrate a correlation between the absence of MSL, in L. infantum isolates from a collection, and the in vitro resistance phenotype, 34 identified in our Phase 2 clinical trial well characterized isolates. 32 , 33 …”
Section: Introductionmentioning
confidence: 70%
“…23 Moreover, recent studies in Brazil, one of the most affected countries to leishmaniasis burden, demonstrated the absence of decreased susceptibility to miltefosine in L. infantum for the 73 strains tested. 24 Although the use of miltefosine has simplified the treatment, severe gastrointestinal side effects can be observed and, after the identification of some cases in endemic areas, 25 recently resistance to this drug was first reported in clinical studies. Some patients relapsed after 9-12 months after successful treatment with this drug and, additionally, its use limitations include teratogenicity and abortifacient nature, which prevents its use in pregnancy.…”
Section: Paromomycinmentioning
confidence: 99%
“…23 Moreover, recent studies in Brazil, one of the most affected countries to leishmaniasis burden, demonstrated the absence of decreased susceptibility to miltefosine in L. infantum for the 73 strains tested. 24…”
Section: Treatmentmentioning
confidence: 99%
“…In further studies, it was suggested that this genomic region, named miltefosine sensitivity locus (MSL), confers natural resistance to the drug [ 26 ]. Although many Brazilian L. infantum isolates do not carry the MSL [ 27 ], its association with miltefosine resistance in vitro is not clear [ 28 ].…”
Section: Introductionmentioning
confidence: 99%